2006
DOI: 10.1186/1476-4598-5-62
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian epithelial cancer: a role for PGE2-synthesis and signalling in malignant transformation and progression

Abstract: Background: The involvement of the cyclooxygenases (COX), in particular COX-2, is well documented for many tumours, e.g. colon, breast and prostate cancer, by both experimental and clinical studies. There are epidemiological data from subjects using NSAIDs, and experimental evidence supporting the hypothesis of prostaglandins (PGs) as regulators of tumourigenesis in the ovary. One of the end products of PG-synthesis, PGE 2 , regulates several key-processes, which are characteristic for tumour growth, e.g. angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Secreted PGE2 acts in either an autocrine or paracrine manner through its four cognate G protein-coupled receptors, EP1 to EP4. Many studies have found PGE2 associated with tumors of the colorectal organs, lung, and breast [57]. In some before studies of our research teams, we have found some cytokines high expressed in endometrial cancers [8, 9], and PGE2 is one of them.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Secreted PGE2 acts in either an autocrine or paracrine manner through its four cognate G protein-coupled receptors, EP1 to EP4. Many studies have found PGE2 associated with tumors of the colorectal organs, lung, and breast [57]. In some before studies of our research teams, we have found some cytokines high expressed in endometrial cancers [8, 9], and PGE2 is one of them.…”
Section: Introductionmentioning
confidence: 71%
“…Recent studies have suggested that PGE2 may be a mitogen associated with a variety of tumors [57, 20]. We performed immunohistochemistry (IHC) in normal endometrium and endometrial cancer tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of proteins related to the prostaglandin synthesis pathway using IHC showed expression of COX-2, microsomal prostaglandin E synthase-I (mPGES-I), and the prostaglandin E 2 receptors EP 1 and EP 2 to the OC stroma, particularly in tumors of higher histological grade (117). …”
Section: Other Moleculesmentioning
confidence: 99%
“…Also, it has been shown that androgen and androgen receptors promote Bax-mediated apoptosis in prostate cancer cells (Lin et al 2006). Furthermore, it is known that PGE 2 promotesthe proliferation and survival of cells through apoptosis inhibition (Sheng et al 1998, Rask et al 2006.…”
Section: Introductionmentioning
confidence: 99%